(untitled) (Prilozi za orijentalnu filologiju, 2017)
In the present paper the author throws more light on the social, political, religious, literary, and cultural aspects of the dervish orders in the Yugoslav lands at the time of Ottoman rule (XIV - XIX century), and especially in Bosnia and Herzegovina, Macedonia, Kosovo, and partly in Serbia. It is well known that the dervishes participated in the conquest of Yugoslav lands by the Turks, in the founding of settlement, the spreading of Islam, and in Islamic oriental culture and literature. By way of illustration the present author dis- cusses the fırst missionaries: Ayni-Dede and Shamsi-Dede, dervish Khorasani in Bosnia, and Meddah-Baba, who is considered the conqueror of Skopje. It is well known that there was a coalition of Ottoman authorities and the Orthodox Sufı orders: Mawlawi, Naqshibenđi, Halveti, Qadiri, Rifai, and others, whose institutions were founded mostly by the wealthy Ottoman aristocracy, the chief representatives of the Ottoman authorities in these parts, as well by the others, and that they were supported by rich endow- ments (waqf). However, the heterodox Sufi orders, the Khurufis, Khalendaris, Khaidaris, Hamzawis, Bektashis, and others, and especially those with shii and alewi tendencies, were in opposition to the Ottoman authorities and the Ottoman social order. Some of them recognized the Shah of Iran as their lavvful ruler, whom them supported, and on whose behalf they rebelled. As an example of this attitude, the present author describes the social and political situation and the rebellious character of the Hamzawi in Bosnia and Herzegovina, at the head of which Shaikh Hamza Bali stood in the 15th century (he was executed in 1573, together with his twelve caliphs at Tahtakale in Istanbul). As an order (brotherhood) the Hamzawis had an independent intemal organization - courts of law, and other things, and acted as an independent body within the Ottoman Empire. In an uprising in 1582, the Hamzawis formed a govemment: Mehmed, son of Hassan, was to be Sultan, Hussein-agha, the vizier, Memi, son of Iskander - defterdar, Ali-Khavadja - qadi-asker, etc., and this government was supposed to take over when the time čame. Therefore they were executed immediately, so that hardly any memory of them and their important representatives remained in later epochs. The author emphasizes especially the role of the Bektashis in the Southern region of our country (Macedonia and Kosovo) where this order was widely spread, and the number of its tekkes proved convenient for political activity. Their influence among the janissaries was also well-known. The pashas of the Bektashi order, called the “Pashas of Tetova” (Macedonia), ruled over the greater part of Central and vvestern Macedonia and Albania with consid- erable independence for more than a century. One of the prominent members of the family, Redjep-Pasha was considered the founder of the Bektashi tekke of Sersem Ali-Baba at Tetovo in the second half of the 18th century. Not only the “Pashas of Tetova”, but also the landovvners, janissaries, craftsmen, and partly free peasants belonged to the Bektashi order. The influence of the Bektashis in the Southern part of the country did not last long, so that in the fifties of the 20th century the çenter of the Bektashis was transferred to Gjakova in Kosovo, when Khazim-Baba became the head of the order for the entire Balkan area (Macedonia, Kosovo, Albania). The order of Naqshibendis played a similar role and exercised similar influence in Bosnia and Herzegovina, according to the author of the present paper. Two great representatives of the tariq were especially prominent: Shaikh Hussein Zukić (died 1799/1800) and Shaikh Sirriya (died 1846/47) an dthe tekken they had founded: the former at the village of Vukeljići, and the latter, at Oglavak, also in the vicinity of Fojnica. Shaikh Sirriya and his Oglavak Tekke was especially influential, and many a governor of Bosnia and Herzegovina čame to visit and converse: Mehmed Vedjih-pasha, Kamil- -pasha, the Governor of Herzegovina Galib Ali-pasha Rizvanbegović, then Omer-pasha Latas, and the leader of the independence movement of Bosnia - Hussein Captain Gradaščević. According to the author, the Shaikh of the Halvetian order, who in 1848 was appointed Shaikh of the Halvetian tekke at Buna near Mostar, with the task of observing the work of the Herzegovinian Governor Ali-pasha Rizvanbegović, and other Herzegovinian aristocrats, who in the opinion of the govrn- ment in Istanbul, had become too independent, had close connections with the Court. The author emphasizes that close ties and cooperation existed between the dervish orders and the Ottoman authorities, although the degree and the extent of cooperation varied. For the frequent uprisings and re- bellions were connected with the activities of the sufi brotherhoods: the rebellion of the Hamzavi in Bosnia, of the Halveti at Užice, with Shaikh Muhammad at its head (executed in 1850 near Rozaj), the Sarajevo uprising led by Shaikh Khaimi, the head of the Qadiri Mustafa-pasha’s (Sinan’s) tekke in Sarajevo in 1682, etc. According to the author of the paper, the dervish orders represented a kind of popular Islamic religion, since their teaching assumed some local color and the cultural influence of the environment in which they lived and func- tioned. In their theory and practice, deposits of foreign religions and cult can be discerned: popular cults of Central Asia and Anatolia, Anatolian-Christian, and later - Balcanic. Syncretism was especially prominent in the mixed religion of the Bektashis. Hence their tolerance towards other religions, in which some of the histori- ans see the importance of heterodox dervish groups, specially the Bektashis, in the Islamization of the Christian population of Rumelia and the Balkans in the course of the 14th and 15th centuries. The humanitarian aspect of the dervish organizations is of special importance, since numerous dervish institutions had on their premises public kitchens, in which warm meals and free lodgings were available for the poor, the dervishes and travellers. They were Skender-pasha’s tekke in Sarajevo, Issa-bey’s tekke, also in Sarajevo, Sinan-bey’s tekke at Čajniče, Ghazi Husrev-bey’s khanikah also in Sarajevo, the Sersem Ali-Baba tekke at Tetovo, and others. Since the artsın especially poetry and music, had a great psychological ef- fect and the power of arousing ecstatic States among the members of the Sufi orders, in which moments, a mystic, as they believed, communicated directly with the Absolute, literature, and especially poetry, were highly appreciated in dervish circles. The symbols of Sufi literature concentrated around the three following topics: absolute beauty, wine and love, as an inspiration towards beauty. Love in this kind of literature was treated as striving of the human soul towards the Absolute, an irrational impulse, and intimate tie with absolute beauty, an attraction of the human špirit to beauty. The author describes ali the particularities in the literary expression, and topics in the writers of the certain dervish orders. He mentions: Servi the Bosniak (died 1591), Ahmed Sudić (died 1596), Hassan Khaimi (died 1691), Fevzi Mostarac (died 1747), Abdurrahman Sirri (d. 1847), Seyyid Vehhab Ilhami (d. 1821/1822), Fadil-pasha Ferizović (d. 1892), etc.